Management of Chronic Liver Diseases Recent Advances - Qi, Xingshun (IntechOpen, 2018)
This book is contributed by worldwide experts in the field of liver diseases. It comprises of 3 sections and 6 chapters to introduce the intra-abdominal hypertension and abdominal compartment syndrome in chronic liver diseases, ascites with hyponatremia, acute kidney injury, portal vein thrombosis, spontaneous bacterial peritonitis in liver cirrhosis, and the use of stereotactic body radiation therapy in hepatocellular carcinoma. Clinicians and investigators who are interested in the management of chronic liver diseases will be acquainted with its merits and usefulness.